The Artist's Freedom : about censorship in Iceland - Karen Dúa Kristjánsdóttir 1982- (2013)
Verkefnið er lokað til 13.5.2020. Censorship has not been a prominent problem in Icelandic arts. Nevertheless, the discussion about censorship in the Icelandic art world has surfaced in recent years. But is Icelandic art actually censored? How free is an Icelandic artist? What defines his/her freedom? The thesis tries to answer whether censorship is a genuine phenomenon in the Icelandic art world or not. It is clear that any artist’s freedom is defined first and foremost by social boundaries, i.e. laws and morals. The laws that have the strongest connection to artists are those concerning the freedom of expression, which is protected under the 73rd article of the Icelandic constitution and the Copyright Act no. 73/1972. Artists are also bound to go by ethical rules, society’s unwritten laws. By crossing the line between what is accepted and what is not, the artist can provoke society’s reaction and even use it to his advantage. When authorities interfere with art, allegedly for the sake of the common good, that can lead to censorship. Many examples of censorship can be found in art history, but the Icelandic examples are not many. Here, five Icelandic examples of possible censorship are examined in depth. The oldest is from the 1940s and the newest from 2012. Some of the cases were abuse of authority. Others were not censorship, as the artists themselves provoked intentionally the negative response that they got. The conclusion is that none of the cases examined here constitutes censorship. Ritskoðun hefur ekki verið áberandi vandamál í íslenskri myndlist. Engu að síður hefur þó umræðan um ritskoðun í íslenska listheiminum opnast á síðustu árum. En er íslensk myndlist raunverulega ritskoðuð? Hversu frjáls er íslenskur listamaður? Hvað afmarkar frelsi hans/hennar? Ritgerðin leitast við að svara spurningunni um það hvort ritskoðun sé raunveruleg í íslenska myndlistarheiminum eða ekki. Ljóst er að frelsi listamannsins afmarkast fyrst og fremst af þjóðfélagslegum höftum, þ.e. lögum og siðferði. Þau lög sem helst ...